BBA: A binary bat algorithm for feature selection - Nakamura, R. Y M [UNESP]; Pereira, L. A M [UNESP]; Costa, K. A. [UNESP]; Rodrigues, D. [UNESP]; Papa, João Paulo [UNESP]; Yang, X. S. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Feature selection aims to find the most important information from a given set of features. As this task can be seen as an optimization problem, the combinatorial growth of the possible solutions may be in-viable for a exhaustive search. In this paper we propose a new nature-inspired feature selection technique based on the bats behaviour, which has never been applied to this context so far. The wrapper approach combines the power of exploration of the bats together with the speed of the Optimum-Path Forest classifier to find the set of features that maximizes the accuracy in a validating set. Experiments conducted in five public datasets have demonstrated that the proposed approach can outperform some well-known swarm-based techniques. © 2012 IEEE.
Keywords: bat algorithm; feature selection; optimum-path forest; Data sets; Exhaustive search; Optimization problems; Optimum-path forests; Selection techniques; Wrapper approach; Feature extraction; Forestry; Algorithms; Automatic Control; Optimization; Problem Solving; Techniques